Interactive Live Streaming: Analysis of Online Marketing Communication in Online Shopping - Ainil Mardiah; Susi Evanita; Larisya Syawalki (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The purpose of this study is to determine and analyze how consumers perceive the added value when shopping through interactive live streaming, their interest in sales conducted via interactive live streaming, and their confidence in online stores that carry out interactive live sales promotions. Data collection techniques include interviews, observation, data sources (informants), and documentation. The data analysis technique used involves presenting data and drawing conclusions. In summary, this research provides valuable insights into the multifaceted effects of interactive live streaming within the context of online shopping. The findings underscore the importance of added value, consumer interactions, and seller trust in shaping consumers' online shopping experiences. These insights carry significant implications for businesses seeking to optimize their online presence and customer engagement strategies.